PERANCANGAN ENSIKLOPEDIA PARIWISATA ALAM KOTA PAGAR ALAM - Ahmad Fikri Maulana; Heri Iswandi; Hardono Wisnu Wijaya (UNIVERSITAS INDO GLOBAL MANDIRI, 2016)
Nature tourism in the city of Pagar Alam should be kept clean and beauty, so that tourists both from Indonesia and abroad to come on holiday to the bustling city of Pagar Alam. Pagar Alam as Nature Tourism destination in South Sumatra should be more active in promoting the city is and add to the existing facilities for the convenience of visitors. Therefore designed a media campaign in the form of the encyclopedia, which presents the complete information about the nature of tourism in the city of Pagar Alam. Encyclopedia provides information and photograph the sights, to make visitors interested in coming to the City of Pagar Alam